Daman and Diu Draft Annual Plan 2006-2007 - Planning Commission (Planning Commission, 2006)
The Union Territory of Daman and Diu is situated on the Western Coast of India on Arabian Sea and surrounded by the State of Gujarat. Its population as per 2001 Census is 158 thousands (92 thousands males and 66 thousand females). It comprises two districts viz. Daman and Diu separated by about 800 kms from one another. Daman has an area of 72 Sq.Kms spread over 22 Villages and one town while Diu has an area of 40 Sq.Km spread over 4 Villages and one town. Both the districts are urbanised since five centuries ago and have Urban Local Bodies (Municipal Councils). About 37 % of population is in urban area. Daman is the Head Quarter of this U.T. which is surrounded by Valsad District of Gujarat State.
Department of Planning and Statistics, Union Territory Administration of Dadra and Nagar Haveli